Identification of insufficiencies and actions taken to improve the skills in the methodological and educational work of the teachers of the Department of Morpho-physiology of Agricultural Sciences, University of Camagüey, Cuba - Mugarra Romero, Carmen (2019)
This work was carried out during the academic year 2016-2017 in the Department of Morphophysiology, Faculty of Agricultural Sciences, University of Camagüey. Observations were conducted during the teaching activities and surveys were carried out to 19 teachers and 42 students, to obtain the initial situational diagnosis that allowed to determine the possible inefficiencies in the educational teaching process. With this, a package of actions was elaborated with a view to perfecting the competences of teachers in methodological and educational work.